2014
DOI: 10.5152/tjar.2014.2220141
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Haemodynamic Optimisation

Abstract: 56During the latest years, a number of studies have confirmed the benefits of perioperative haemodynamic optimisation on surgical mortality and postoperative complication rate. This process requires the use of advanced haemodynamic monitoring with the purpose of guiding therapies to reach predefined goals. This review aim to present recent evidence on perioperative goal directed therapy (GDT), with an emphasis in some aspects that may merit further investigation. In order to maximise the benefits on outcomes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 108 publications
0
2
0
Order By: Relevance
“…Despite the higher cardiac output, other research studies demonstrated that elevating MAP with noradrenaline above 65 mmHg on balance was not linked to better organ perfusion. In these studies, however, an increase in cardiac output following the first MAP escalation step from 65 to 75 mmHg was not clinically significant (>10%), and additional MAP increases in those studies did not appreciably increase the cardiac output (5,10).…”
Section: Mean Arterial Pressure (Map)mentioning
confidence: 71%
See 2 more Smart Citations
“…Despite the higher cardiac output, other research studies demonstrated that elevating MAP with noradrenaline above 65 mmHg on balance was not linked to better organ perfusion. In these studies, however, an increase in cardiac output following the first MAP escalation step from 65 to 75 mmHg was not clinically significant (>10%), and additional MAP increases in those studies did not appreciably increase the cardiac output (5,10).…”
Section: Mean Arterial Pressure (Map)mentioning
confidence: 71%
“…Only 10-15% of surgical procedures are performed on high-risk patients, yet they are responsible for more than 80% of deaths. Patients who are admitted to the intensive care unit after receiving initial postoperative treatment in a normal ward have the highest mortality rates of almost 39% in this demographic (5). Perioperative haemodynamic strategies are also referred to as goal-directed therapy (GDT) and have been designed in an effort to reduce morbidity and mortality among patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings from our study resonate with the conclusions of previous research which underscore the crucial role of nursing interventions in optimizing postoperative care outcomes. 13 One study 14 found that patients who received additional nursing care reported better management of symptoms and lower rates of postoperative complications compared to those receiving standard care alone. The objective of the study was to investigate the influence of comprehensive high-quality nursing care on postoperative complications, the degree of pain, and nursing satisfaction in these patients during the perioperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Given the incidence of high morbidity and mortality rates in high-risk surgery patients, ensuring stable and sufficient cardiac output (CO) or cardiac index (CI) is crucial for patients' survival (1)(2)(3). The National Institute for Health and Clinical Excellence (NICE) 2011 has recommended CO monitoring to ensure that perioperative goaldirected therapy optimization correlates with improved postoperative outcomes in moderate-to high-risk surgery patients (4,5). Kidney transplant surgery requires monitoring because of comorbidities, graft staging, renal vessel anastomosis, and ischemia-reperfusion.…”
Section: Introductionmentioning
confidence: 99%